EFFECT DIRECT AND INDIRECT (INQUIRY) INSTRUCTIONS MODEL IN TEACHING GYMNASTICS - Helmy Firmansyah (Publikasi Pendidikan, 2016)
To do the gymnastic floor movement needs a good skill, it is because gymnastic is a physical activity that helps to optimise the growth of children, and also gymnastic give a huge contribution in a basic fundamental moves development which is important to other sport activities, especially in terms of how we control the body efficiently and effectively. There are some problems in the implementation of gymnastics, like the students are afraid to do it, feel aching of their body after doing gymnastics, and they also have trauma for it, etc. Those things are caused of unsatisfied result of the lessons or they could not achieve minimum score in gymnastic subject. Therefor, the researchers used direct and indirect ( inquiry ) instruction lessons to comprehend the differences between them in gymnastic subject. The method which used is an experiment with Pre-test Post-test Control Group Design. The population of this research is 200 students of SMA N 1 Haurgeulis in 10 grade and using random technique simple which is 40 students as samples. The instrument used in this study was the measurement of psychomotor measurement. Based on calculations and data analysis can be concluded that for direct instruction obtained p-value (0.000) <α (0.05) then H0 is rejected. For indirect instruction (inquiry) obtained p-value (0.000) <α (0.05) then H0 is rejected. The conclusion of this study is that there is a direct influence learning direct and indirect (inquiry) instructions with the result of gymnastic subject in SMA N 1 Haurgeulis.Keywords: direct, indirect instruction, gymnastics